Roznice w efektywnosci wykonywania wybranych czynnosci z pilka pomiedzy reprezentacja; Polski, a najlepszymi druzynami XVII Mistrzostw S'wiata w Pilce Noznej (Korea Pld. - Japonia - 2002) - Buraczewski, T. (Polish Journal of Sport and Tourism, 2009)
The purpose of this study was to demonstrate differences in effectiveness of ball handling by Polish players in confrontation with those of best teams during the 17th Football World Cup (South Korea and Japan . 2002). Research material consisted of data describing ball handling by Polish players (all games played) and payers of the best teams in the tournament . i.e. Brazil and Germany (starting from 1/8 final). The basic method of data collection involved DVD game recordings combined with objective observation sheet, used for recording of the tested elements of ball handling. In this study the following technical elements were tested: passes, shots at the goal, 1x1 play in defence and in attack and slide tackle. Upon completion of the research it was found that the effectiveness of ball handling by the Polish national team was inferior to ball handling by two top teams of the tournament. These differences mainly involved the quality of passes and 1x1 playing skills (p.0.05). Differences in the effectiveness of ball passing involved most of passing directions, their reach (length) as well as passes after receiving of the ball (p.0.05). As far as the effectiveness of 1x1 playing was concerned the Polish team was far behind the top teams, particularly including attack, and especially header duels on the teams own half of the field as well as on the opponents' half of the playing field (p.0,05). As far as shots and slide tackles were concerned our players were not any inferior to the top teams of the world.